Personal Branding Beauty Influencer di Instagram terhadap Persepsi Followers - Febriani Angellina; Ahmad Junaidi (Kiwari, 2023)
Apart from being used as a new forum for communication, social media is also used as a medium for self-expression and building personal branding. Personal branding is an assessment related to skills, attitudes and performance that is formed by individuals and aims to show self-concept in the eyes of others. Likewise, what was done by @tasyafarasya, a popular beauty influencer in Indonesia who built her personal branding through Instagram social media. Currently, Tasya Farasya has 5.8 million Instagram followers as of September 2022. The personal branding built by Tasya Farasya on Instagram social media influences followers' perceptions of her. this study has the aim to show whether there is any influence from personal branding beauty influencer Tasya Farasya on Instagram social media on the perceptions of her followers and what are the personal branding beauty influencer Tasya Farasya's concepts that are dominant among the 8 personal branding concepts initiated by Peter Montoya. The theory of this research is the Eight Concepts of Personal Branding initiated by Peter Montoya. This type of research approach is quantitative through the spread of a list of questions to 100 people who are Tasya Farasya’s Instagram followers. The data obtained were then analyzed with several tests, namely the correlation coefficient test, the coefficient of determination test, and simple regression analysis. The results of this analysis show if there is a strong relationship between the two variables, as well as the influence of Tasya Farasya's personal branding on Instagram and contributing 69.6% to the perception of her followers and the personal branding beauty influencer Tasya Farasya's concept which is dominant is the concept of specialization of ability indicators, the concept of visible, the concept of leadership, and the concept of firmness. Media sosial selain dijadikan sebagai wadah baru dalam berkomunikasi, dijadikan juga sebagai media untuk mengekspresikan diri dan membangun personal branding. Personal branding adalah sebuah penilaian yang berhubungan oleh keterampilan, sikap, serta kinerja yang individu bentuk dan bertujuan untuk menunjukkan konsep diri di mata orang lain. Begitu pula yang dilakukan oleh @tasyafarasya, seorang beauty influencer yang populer di Indonesia yang membangun personal branding-nya melalui media sosial Instagram. Saat ini Tasya Farasya memiliki followers Instagram sebanyak 5,8 juta per September 2022. Personal branding yang dibangun oleh Tasya Farasya di media sosial Instagram mempengaruhi persepsi followers kepadanya. Penelitian ini mempunyai tujuan yaitu untuk melihat adakah pengaruh dari personal branding beauty influencer Tasya Farasya di media sosial Instagram terhadap persepsi followers-nya dan apa saja konsep personal branding beauty influencer Tasya Farasya yang dominan diantara delapan konsep personal branding yang dicetuskan Peter Montoya. Pendekatan penelitian ini yaitu kuantitatif dengan melakukan penyebaran kuesioner terhadap 100 responden yang merupakan pengikut Instagram Tasya Farasya. Data yang didapatkan kemudian dianalisis dengan beberapa uji yaitu uji koefisien korelasi, uji koefisien determinasi, dan analisis regresi sederhana. Perolehan dari analisis ini menunjukan ditemukan hubungan tinggi diantara kedua variabel, serta pengaruh personal branding Tasya Farasya di Instagram berpengaruh dan memberikan kontribusi 69,6% terhadap persepsi followers-nya dan konsep personal branding beauty influencer Tasya Farasya yang dominan adalah konsep spesialisasi indikator kemampuan, konsep terlihat, konsep kepemimpinan, dan konsep keteguhan.